Comparison of Two Models of WLC and TOPSIS in Land suitability analysis for urban development (Case Study: Foman and Shaft) - Hamide Aliani; Mohadeseh Ghanbari Motlagh; Mansour Halimi (تحقیقات کاربردی علوم جغرافیایی)
In many developing countries, including Iran, urban development is one of the most important factors in land use change. Most cities, in their turn, have caused the destruction of agricultural land and have been covered by urban expansion. This is a matter of economic and agricultural activity, especially in province like Gilan, due to temperate climate and fertile soil, which is one of the things that demands that appropriate planning prevent the uncontrolled expansion of these cities. In this regard, we aimed to study the land suitability analysis as a tool for planning and predicting an optimal urban development model in cities under the multi criteria decision making (WLC and TOPSIS models) in the GIS and based on various indicators at Foman and Shafts in western Gilan. The results showed that the output classification of the two models used was different, but suitable areas for urban development were overlapping in two methods. The most suitable areas for urban development are found in northern and eastern parts. Also, land use has the highest importance in zoning. Based on the results, the inner development of the cities is recommended as the first priority.